Banners Forward: the rise of a new women's movement from below in Argentina, 2003. - Green, Romina. (2017)
Abstract: In August of 2003, the 18th Encuentro de Mujeres (Women's Encounter) was organized in the city of Rosario, Argentina. The Encuentro was not a new occasion because since 1985 it had become a yearly Argentine feminist event. The year 2003 did not mark a special anniversary in the struggle for female emancipation in Argentina nor around the world; yet, this particular conference proved to be a turning point for the women's movement in Argentina. In this thesis, I seek to explore and analyze the reasons for the momentous influx by women from below into the broader women's movement. The 2003 Encuentro in Rosario stands as the crux in which the movement became a social movement, initiating the breaking of the long-standing silence surrounding the abortion taboo. I argue that women from below organically transformed the women's movement in 2003 into a new women's movement embedded by the memories of state violence of the 1970s and 1980s, as well as the experiences of economic discord and the new social movements during the 1990s.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of History.; Advisor: Peter Winn.; Committee: Virginia Drachman.; Keywords: History, Latin American history, and Gender studies.